Pengaruh Beban Kerja Terhadap Burnout Perawat pada Ruang NICU RSUD Bima - Nursani Nursani; Fai Nando; M. Ahyar Putra (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the effect of workload on the level of burnout among nurses in the NICU at Bima General Hospital. The research employs a quantitative approach with a causal associative design, involving 37 nurses as respondents, who were surveyed using questionnaires. Regression analysis results indicate that workload has a positive and significant effect on burnout, with a t-statistic value of 2.840 (p = 0.007), meaning that the higher the workload, the greater the level of burnout experienced by nurses. These findings underscore the importance of effective workload management to prevent burnout, improve nurses' well-being, and ensure optimal service quality in the NICU.